Closure of tracheoesophageal puncture with pedicled fascia flap of the sternocleidomastoid muscle. Issue 4 (August 2015) - Wasano, Koichiro; Suzuki, Noriomi; Kawasaki, Taiji; Yamamoto, Sayuri; Minami, Shujiro; Yamashita, Taku; Ogawa, Kaoru
Abstract: Objective: Closure of a tracheoesophageal puncture (TEP) formed during voice prosthesis implantation may sometimes be required. We report a new method of closure that we have termed the RESET method. Methods: We used the RESET method for four patients. An initial incision was made at the mucocutaneous junction of the tracheostoma, and the trachea and esophagus were separated. The TEP was sectioned, and the tracheal and esophageal sides were sutured into separate layers. A pedicled fascia flap lifted from the sternocleidomastoid muscle was sandwiched between the trachea and the esophagus, and subsequently secured. Results: The TEP was closed in all patients, and no complications were observed. Conclusion: The RESET method, using a pedicled fascia flap with stable perfusion, is a simple, reliable method of TEP closure.